Industrial drying of foods (London, 1997)
The book provides a basic understanding of the physical and chemical processes that underlie food-drying operations. Comprehensive descriptions of different types of dryers available to industry are given and factors affecting the operation, control and selection of dryers are described
Keywords: food - drying - equipments and supplies